О роли электропривода в решении проблемы энергосбережения в Украине - Клепиков, Владимир Борисович; Розов, Владимир Юрьевич (НТУ "ХПИ", 2008)
Based on the situation in Ukraine, exceptionally high efficiency of saving of the fuel energy resources is justified due to modernization of mean power electrical drives through transfer to the controlled electrical drive. It is explained by the fact that such electrical drive, being optimizing technique of technological process, provides for economy of the materials with its energy constituent often significantly exceeding decrease in real electrical energy loss. Primary tasks and measures aiming for modernization organization are specified.
On the role of electrical drive in solution of the problem of energy resources saving in Ukraine
Keywords: топливо; энергоемкость; электростанция тепловая; электроэнергия; модернизация; двигатель асинхронный; мощность; электропривод частотно-регулируемый